Impact of Pandemic on Socio-Economic Dynamics of Modern India (International Journal of Food and Nutritional Sciences, 2022)
The COVID-19 pandemic established an adverse link between economics, the environment, and human health. The economy is also affected due to a pandemic situation where the purchase of non-essential things has been temporarily paused during the lockdown. people can go shopping for only their basic needs. All the changing patterns can offer opportunities for the implementation of long-term sustainable changes. This Global crisis has changed the patterns of electricity consumption during this pandemic. Most individuals work from home and have more flexible schedules because do electricity required for a home is increased than the office place.